A comparative study of coal fly and bottom ashes as sustainable electroactive vibration damping materials - Begen, Deniz; Calis-Ismetoglu, Gokce; Gumus, Omer Yunus; Unal, Halil Ibrahim (Korean Soc Environmental Engineers - Ksee, 2024)
Coal is used in most of the power and chemical plants to meet energy needs which produce various waste ashes. Reuse of these ashes as electroactive materials has great importance for sustainable development. In this study, it was detected that the main components of coal fly (CFA) and bottom ashes (CBA) were oxides of silica (SiO2), 2 ), iron (Fe2O3), 2 O 3 ), aluminium (Al2O3), 2 O 3 ), and magnesium (MgO), besides carbon. These are well-known electrorheological (ER) active materials. The aim of this study is to reveal dielectric and electroactive vibration damping capabilities of CFA and CBA. According to the dielectric and ER flow tests carried out in insulating silicone oil (SO), the optimum concentration of particles was determined to be 35 wt.% for both ashes. Higher ER yield stress (tau y tau y = 135 Pa), higher ER efficiency (32.8), and better viscoelastic properties (tau c= tau c = 128 Pa, G' = 680 kPa) under 3.0 kV mm-1 applied electric field were obtained for 35CFA/SO suspension system compared to 35CBA/SO (tau y tau y = 125 Pa, ER eff = 24.0, tau c = 55 Pa, G' = 260 kPa). Although it was concluded that both ashes can be upcycled to sustainable and smart vibration damping alternative materials, better performance was observed for CFA particles.
Keywords: Coal bottom ash; coal fly ash; dielectric; electrorheology; sustainable material; upcycling